Diversity and distribution Patterns of the infralittoral green macroalgae from Potiguar basin, Rio Grande do Norte, Northeastern Brazil - Cocentino,Adilma de Lourdes Montenegro (2010)
Diversity and distribution pattern of the infralittoral green macroalgae at Potiguar basin, Rio Grande do Norte, Northeastern Brazil were analyzed from material collected at depths varying from 2 to 100 m. Collections were carried out with two types of dredges during four campaigns: July 2002, May and November 2003 and May 2004 at 43 stations. Chlorophyta is represented by 54 species, five varieties and three forms. The most representative family is Caulerpaceae, and the most diverse genus is Caulerpa, with 11 species. The results showed that most taxa (89%) are rare, and 10% are present at low frequencies. The most frequent species was Caulerpaprolifera (Forssk.) J.V. Lamour. occurring at almost all coastal and inner shelf stations, recorded in all campaigns. Species distribution by depth range showed that higher species number occurred on the inner shelf from 10 to 20 m, and a wide vertical distribution pattern was registered for Anadyomenestellata (Wulfen in Jacq.) C. Agardh,Chamaedoris peniculum (J. Ellis & Solander) Kuntze, Codium isthmocladum Vickers, Microdictyon sp., Udoteaoccidentalis A. Gepp & E. Gepp and Ventricaria ventricosa (J. Agardh) J.L. Olsen & J.A. West. Four species, Cladophoracoelothrix Kütz., C.ordinata (Børgensen) C. Hoek, Caulerpellaambigua (Okamura) Prud'homme & Lokhorst and Halimedasimulans M. Howe, were recorded for the first time in Rio Grande do Norte.